2012
DOI: 10.1185/03007995.2012.744302
|View full text |Cite
|
Sign up to set email alerts
|

A review of intranasal ketorolac tromethamine for the short-term management of moderate to moderately severe pain that requires analgesia at the opioid level

Abstract: Based on the clinical trials reviewed, IN ketorolac was associated with significant pain reduction in patients with various post-operative procedures, with good tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The incidence of adverse events was similar to that of placebo group. Notably, gastrointestinal bleeding was not associated with ketorolac group …”
Section: Intranasal Ketorolacmentioning
confidence: 88%
See 1 more Smart Citation
“…The incidence of adverse events was similar to that of placebo group. Notably, gastrointestinal bleeding was not associated with ketorolac group …”
Section: Intranasal Ketorolacmentioning
confidence: 88%
“…The recommended dosage of ketorolac tromethamine (oral, IM, IV) for subjects aged > 65 years is half of the dosage used for patients aged < 65 years of age (typically 30 mg for single doses), and a total daily dose should not exceed 60 mg when multiple doses are used . Ketorolac is not recommended for use in pediatric patient age group.…”
Section: Chemical Structure and Pharmacologymentioning
confidence: 99%
“…Ketorolac is a mixed cyclooxygenase 1/2‐inhibitor. It is FDA approved for moderate to severe pain in an oral, intravenous, and more recently, a nasal spray (NS) formulation . NS formulations in general offer several advantages to migraine patients; these include faster absorption than oral agents as well as the ability to utilize such medication formulations even when patients are nauseated and cannot or do not want to swallow a tablet or use more invasive parenteral therapies .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients received less opioids (11). He et al (15) in a systematic review in 2012, reported that using intranasal ketorolac spray can significantly reduce postoperative pain of patients. Yet, no comprehensive study is available on the application of intravenous and intranasal ketorolac in patients undergoing maxillofacial fracture surgeries.…”
Section: Introductionmentioning
confidence: 99%